Effects of the Yangjing Capsule Extract on Steroidogenesis and Apoptosis in Mouse Leydig Cells. (13th November 2012) - Sun, Dalin; Cui, Yugui; Jin, Baofang; Zhang, Xindong; Yang, Xiaoyu; Gao, Chao
Abstract : Objectives . This study aimed to explore the effect and mechanism of Yangjing capsule on testosterone secretion in mouse Leydig tumor cells (MLTC-1). Methods . MLTC-1 cells were treated with the Yangjing capsule extract for 24 h. The testosterone level in medium was measured by radioimmunoassay. The expression of steroidogenic enzymes (StAR, CYP11A1, and HSD3B) in the cells was examined using real-time RT-PCR and immunoblotting. Additionally, MLTC-1 cells were treated for 48 h in a serum-free medium. The cell viability was measured by MTT assay. The cell cycle and apoptosis were analyzed using flow cytometry. The expression of activated caspase-3 was analyzed using RT-PCR and a colorimetric protease assay. Results . The Yangjing capsule extract increased testosterone production and the expression of StAR, CYP11A1, and HSD3B mRNAs and proteins compared with the control. H89 significantly inhibited these effects. The medicine improved the viability of MLTC-1 cells, decreased the number of cells in G0/G1 phase, and increased the number of cells in S-phase, as well as prevented cell apoptosis by inhibiting caspase-3. Conclusion . The Yangjing capsule can stimulate MLTC-1 cells to secrete testosterone and may be an alternative treatment for diseases characterized by insufficient testosterone production.